The situation of application of theachers' strategies towards the prevention and modification of the unwanted behaviors in the class - Kazu, Hilal (My University, 2007)
The aim of this study is to determine the situations of application of the teachers' strategies towards the prevention and modification of unwanted behaviors in the class. A survey method was used in the study. The sample of the study is consisted of 748 teachers who had been working in the primary schools the city of Elaz?? during 2003-2004 instructional year. In this article the findings towards application of the strategies for the prevention and modification of the misbehaviors of the students were discussed; and according to the results some recommendations were developed.
Ö?retmenleri?n sinifta i?stenmeyen davranişlarin önlenmesi?ve de?i?şti?ri?lmesi?ne yönel?ik strateji?leri?uygulama durumlari
Keywords: Classroom management; The Strategies towards the prevention and modification of misbehaviors; Unwanted behaviors (Misbehaviors)